2010
DOI: 10.1177/1753465810374610
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy for allergic rhinitis: a prospective, randomized, single-blind, placebo-controlled study

Abstract: This study demonstrates that phototherapy may be an effective modality in the treatment of allergic rhinitis especially in cases of which commonly used drugs either are contraindicated and/or have insufficient efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 9 publications
0
26
1
2
Order By: Relevance
“…TNSS was recorded before commencing the trial and one month after the trial. Both groups noted a reduction in TNSS however this was more so in the active treatment group, which noted a statistically significant change (p<0.001) [48].…”
Section: Phototherapymentioning
confidence: 82%
“…TNSS was recorded before commencing the trial and one month after the trial. Both groups noted a reduction in TNSS however this was more so in the active treatment group, which noted a statistically significant change (p<0.001) [48].…”
Section: Phototherapymentioning
confidence: 82%
“…Em geral, a luz vermelha causa o aumento da quantidade de oxigênio no sangue da mucosa nasal fazendo com que o organismo atue de forma mais rápida na eliminação das substâncias inflamatórias, na redução do inchaço nasal e no desentupimento das cavidades nasais o que permite a passagem de ar e leva o organismo humano potencializar a desintoxicação da mucosa nasal [14,15].…”
Section: Resultsunclassified
“…Segundo o estudo de [14] a fototerapia é um tipo de tratamento eficiente, pois induz um efeito imunossupressor ao organismo, causando a omissão da liberação de mediadores químicos, além de realizar terapia anti-inflamatória. Além disso, este seria um modo de tratamento alternativo eficaz para quando o uso de fármacos são contra-indicados e/ou não possuem resultados satisfatórios para alguns pacientes [15].…”
Section: Discussõesunclassified
“…Statiscally significant differences were found in the average results of the Rhinoconjunctivitis Quality of Life Questionnaire (Cingi, et al, 2009). Another prospective, randomized, single-blind study showed that total nasal scores decreased in both mUV/VIS and low-intensity visible light (mUV/VIS without UV) treated groups (Cingi, et al, 2010). But the decrease was highly significant in the mUV/VIS treated group when compared with the low-intensity visible light treated group.…”
Section: Phototherapy In Allergic Rhinitismentioning
confidence: 99%